2017
DOI: 10.1007/s13193-017-0640-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients with Cervical and Vaginal Stump Carcinomas Treated with More Conservative Surgical Approaches: a 9-Year Experience of a Tertiary Oncology Center

Abstract: The surgical management of stump carcinoma includes the gold standard pelvic exenteration and more conservative approaches. This study aimed to investigate the outcome among a cohort of vaginal and cervical stump carcinomas that were treated with an intent of organ preservation. This is a prospective study of 60 patients with a biopsy confirmed stump carcinomas at a tertiary care oncology center in Egypt. The demographic, surgical, and pathological data were collected and patients underwent radical surgery wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…1 Regarding localized recurrence, local excision has been the primary treatment option, in which precise surgical margin is critical. 2 Hegazy et al reported no increase in mortality after local tumor resection with disease-free resection margins. This indicates that strict margins for resecting vaginal stump recurrence could improve outcomes.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…1 Regarding localized recurrence, local excision has been the primary treatment option, in which precise surgical margin is critical. 2 Hegazy et al reported no increase in mortality after local tumor resection with disease-free resection margins. This indicates that strict margins for resecting vaginal stump recurrence could improve outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Hegazy et al reported no increase in mortality after local tumor resection with disease‐free resection margins. This indicates that strict margins for resecting vaginal stump recurrence could improve outcomes 2 . Laparoscopic approaches for treating vaginal stump recurrences have been reported 1 .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations